Social factors and academic stress among higher institution students in Oyo State, Nigeria (2021)
The study investigated nexus between social factors and academic stress among higher institution students in Oyo state, Nigeria. The study adopted descriptive research design of survey type, the population consisted of higher institution students in Oyo state. Simple random sampling technique was used to sample two-hundred and ninety five respondents. Quantitative research instrument was used to elicit information from the selected respondents and data collected was analyzed using Pearson’s Product Moment Correlation and Multiple Regression. The results revealed that there was positive relationship between social factors (peer- pressure, family structure and social activities) and academic stress. Based on the findings, it was recommended that lecturers working in these institutions of higher learning and professional counselors should organize seminars and meetings for concerned students in order to encourage, and advise them on how to manage academic stress, maintain good relationship with their peers and balance social activities with their academics